2005
DOI: 10.1590/s0074-02762005000100018
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral resistance mutations in human immunodeficiency virus type 1 infected patients enrolled in genotype testing at the Central Public Health Laboratory, São Paulo, Brazil: preliminary results

Abstract: Antiretroviral resistance mutations (ARM) are one of the major obstacles for pharmacological human immuno-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…The high prevalence of TAMs (67.24%) was similar to that reported in São Paulo (73%). 24 The K65R mutation was not reported in most national studies and has occurred in less than 1% of the patients in this study. At Brazilian Northeast region this mutation was seen in 3.4% of patients and, specifi cally in the state of Ceará, in 5.9% of cases.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The high prevalence of TAMs (67.24%) was similar to that reported in São Paulo (73%). 24 The K65R mutation was not reported in most national studies and has occurred in less than 1% of the patients in this study. At Brazilian Northeast region this mutation was seen in 3.4% of patients and, specifi cally in the state of Ceará, in 5.9% of cases.…”
Section: Discussionmentioning
confidence: 49%
“…23 In the other Brazilian studies, L90M was also the most frequent, present in 26 to 37% of the cases. 20,21,23,24,44 Compared with international data, these patients present lower prevalence of wild-type virus, probably because in other sites -where genotype was available earlier in the setting of virologic failure -more wild-type virus can be demonstrated. Other reason may be the lower exposure to less effective regimens, including less than two active agents.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The identification of specific drug resistance mutations is increasingly used to avoid antiretroviral drugs that retain only minimal residual activity in favor of other residual activity that is likely to be either fully or almost fully active. Previous national and regional surveillance studies on the prevalence of mutation conferring antiretroviral drug resistance were carried out in large centers in Brazil (3,4,(6)(7)(8)(9)(10). All of these studies have shown a low frequency of wild-type HIV-1 isolates and a high prevalence of virus strains containing resistance mutations among treated patients failing HAART.…”
Section: Introductionmentioning
confidence: 99%